Pound for Pound Export Diversification - James E. Anderson; Yoto V. Yotov (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We propose a short-run model of the extensive margin of trade and deploy it to distinguish and quantify domestic and cross-border margins. Our empirical focus is on the domestic extensive margin of trade (domestic distribution of a product) and its importance for quantifying policy and globalization effects on the international extensive margin of trade. We build a dataset that combines data on the domestic extensive margin and the standard international extensive margin. It reveals significant and intuitive variation in the domestic extensive margin across countries and over time. We quantify the extensive margin effects of European Union (EU) integration, 2008-2018, and demonstrate that these effects cannot be identified without the domestic extensive margin. We find strong and highly heterogeneous effects, both across countries and directionally.
Keywords: F13; F14; F16; 330; extensive margin; domestic extensive margin; globalization; gravity